DEVELOPING GLOVE AND FINGER PUPPETS AS MEDIA FOR TEACHING SPEAKING AT THE FIRST YEAR STUDENTS OF SMP DHARMA PANCASILA MEDAN - Gadis Wulandari; Sumarsih Sumarsih; Puan Suri Mira Anisa Sembiring (Universitas Negeri Medan, 2020)
This study aimed at identifying the students’ needs of SMP Dharma Pancasila Medan in learning speaking using media that is glove and finger puppets. The nature of this study was Research and Development (R & D). The steps were conducting the needs analysis, planning, developing the media, obtaining the experts’ judgments, revising and finally writing the final product glove and finger puppets. This study involved 24 students of the first year students of SMP Dharma Pancasila Medan as the research subjects. The instruments for collecting the data were questionnaires (needs analysis questionnaire and expert judgment questionnaires). The results of the needs analysis questionnaire were analyzed using percentage and the expert judgment were analyzed using descriptive statistics. Data got from the result of need analysis was being the basis in developing the product. The researcher was develop five puppets. All of the puppet was kind of animal: They are caterpillar, bee, ladybug, dragonfly, and butterfly. The puppet are use to help the students in describing animals. Then, based on the expert judgment, the media are appropriate for the first year students of junior high school. It was proved by the mean value of the appropriateness of the media is 3.6. It is categorized as “Very Good” as its positions is in the interval 3.28< x < 4.03.Key words: Teaching Media, Speaking Skill, Glove and Finger Puppets